A quantitative analysis of attitudes toward pornography use in secure hospitals: sexual, violent and non-offenders. Issue 2 (13th May 2019) - Mellor, Emily; Duff, Simon
Abstract : Purpose: The purpose of this paper is to investigate the attitudes of staff members in secure hospitals and the general population towards pornography use and their decision-making regarding access to pornography. Design/methodology/approach: A between participants design was used whereby 324 participants, including 162 staff members and 162 people of general population, answered an online questionnaire. Vignettes were presented of six hypothetical patients in a secure hospital, based on gender (male/female) and offence type (sexual/violent/non-offender). Participants were required to decide whether the individual depicted in the vignette should have access to pornography. Finally, participants were given a psychometric assessment of their own attitudes towards pornography. Findings: Participants were less likely to decide that the sex offender should have access to pornography than the violent or non-offender, thus the offence type of the patient was a significant predictor. There was a significant relationship between attitudes to pornography and whether the individual in the vignette should be given access to pornography. There was no significant difference between attitudes towards pornography of the general public and staff members or for male and female participants. Gender of the patient described in the vignette was not a significant predictor. Practical implications: The research highlights the importance of our own attitudes towards pornography, our possible beliefs about sexual offenders and the effects these may have on decision-making. Originality/value: The research determines attitudes towards pornography and explores how attitudes influence decision-making.